Child Health and the Income Gradient: Evidence from Australia. - Khanam, Rasheda; Nghiem, H.S.; Connelly, L.B. (My University, 2009)
Previous research has shown a strong relationship between household income and child health, in particular for older children, though the actual mechanism involved is uncertain. This article investigates how this income-health gradient might be caused, using data from the Longitudinal Study of Australian (LSAC) on such variables as previous health, household income, birth weight, breastfeeding, gender, nutrition and diet, household size, parent employment and education, parent physical and mental health, and parent lifestyle risk factors. The results show that income has only a small protective effect on child health, possibly due to the extensive and universal public healthcare system in Australia offseting some of the important health-related disadvantages that are associated with low incomes in other countries.
Journal of Health Economics
Keywords: Finance -- Income (Salary and Wages); Health; Finance; Health and wellbeing; Income, wealth and finances; Health; Finance; Income (Salary and Wages); Income, wealth and finances; Health and wellbeing